2015
DOI: 10.11604/pamj.2015.22.62.7264
|View full text |Cite
|
Sign up to set email alerts
|

Les aspects des frottis cervico-vaginaux chez les femmes vivants avec le VIH suivies à Thiès/Sénégal et association avec le degré d’immunodépression

Abstract: De nombreuses études ont démontré que les femmes infectées par le VIH ont un risque accru de survenue de néoplasies cervicales intra épithéliales. L'association entre les deux affections étant bidirectionnelle, l'objectif était de décrire les anomalies cervicales chez les femmes séropositives au virus de l'immunodéficience humaine (VIH), de rechercher des facteurs associés et de proposer des recommandations en termes de suivi de ces femmes. Il s'agissait d'une étude transversale, multicentrique recensant l'ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…The aim of this study was to identify cytological lesions in women living with HIV, in order to provide early treatment, to establish a correlation between the various Previous hospital studies in the general population have reported low rates of cytology abnormalities [18,19,20]. The proportion of cytology abnormalities found in our study was 38.9%, which is higher than the rates reported in several previous studies (19%, 21%, and 22.4% respectively) [21,22,23].…”
Section: Discussioncontrasting
confidence: 49%
“…The aim of this study was to identify cytological lesions in women living with HIV, in order to provide early treatment, to establish a correlation between the various Previous hospital studies in the general population have reported low rates of cytology abnormalities [18,19,20]. The proportion of cytology abnormalities found in our study was 38.9%, which is higher than the rates reported in several previous studies (19%, 21%, and 22.4% respectively) [21,22,23].…”
Section: Discussioncontrasting
confidence: 49%